Whole Resistome Analysis in Campylobacter jejuni and C. coli Genomes Available in Public Repositories - Cobo-Díaz, José F.; González del Río, Paloma; Álvarez-Ordóñez, Avelino (Frontiers in Microbiology, 2021)
Campylobacter spp. are the most frequent agent of human gastroenteritis worldwide, and the spread of multi-drug resistant strains makes the clinical treatment difficult. The current study presents the resistome analysis of 39,798 C. jejuni and 11,920 C. coli genomes available in public repositories. Determinants of resistance to β-lactams (Be) and tetracyclines (Te) were the most frequent for both species, with resitance to quinolones (Qu) as the third most important on C. jejuni and to aminoglycosides (Am) on C. coli. Moreover, resistance to Te, Qu and Am was frequently found in co-occurrence with resistance to other antibiotic families. Geographical differences on Clonal Complexes distribution were found for C. jejuni, and on resistome genotypes for both C. jejuni and C. coli species. Attending to the resistome patterns by isolation source, three main clusters of genomes were found on C. jejuni genomes at antimicrobial resistance gene level. The first cluster was formed by genomes from human, food production animals (e.g., sheep, cow and chicken) and food (e.g., dairy products) isolates. The higher incidence of tet(O), associated with tetracycline resistance, and the gyrA (T86I) single nucleotide polymorphimsm (SNP), associated with quinolone resitance, among genomes from this cluster could be due to the intense use of these antibiotics in veterinary and human clinical settings. Similarly, high incidence of tet(O) genes were found of C. coli genomes from pig, cow and turkey. Moreover, the cluster based on resistome patterns formed by C. jejuni and C. coli genomes of human, turkey and chicken origin, is in agreement with previous observations reporting chicken or poultry related environments as the main source of human campylobacteriosis infections. Most clonal complexes (CCs) associated with chicken host specialization (e.g., ST-354, ST-573, ST-464 and ST-446) were the CCs with the highest prevalence of determinants of resistance to Be, Qu and Te. Finally, a clear trend towards an increase in the occurrence of Te and Qu resistance determinants on C. jejuni, linked to the spread of the co-occurrence of the blaOXA-61, and tet(O)-tet(O/W/O) genes and the gyrA (T86I) SNP, was found from 2001 to date in Europe.